The Role of Bawaslu in Law Enforcement of the 2024 Election in West Nusa Tenggara Province - Kafrawi, Rachman Maulana; Setiawan, Agung; Amalia, Riska Ari (JATISWARA, 2025)
Election general is instrument important for towards a democratic country. Principles of elections nature direct, general, free, secret, honest, fair and periodic known with principle election based on Constitution of the Republic of Indonesia. 1945. Research This aiming for analyze role Election Supervisory Agency in enforcement law 2024 elections in West Nusa Tenggara Province. With understand strategies, challenges, and effectiveness Election Supervisory Agency in supervise implementation election, it is expected can give constructive recommendations​ for increase performance institution This. Research This directed for answer formulation problem through study socio-legal. Socio-legal research represents relatedness between context Where law are (an interface with a context whitin which law exists). Role of the Supervisory Body Election (BAWASLU) in enforcement law Election Simultaneously In 2024 in NTB Province already done with well, that's it This can seen from findings and reports handled with professionalism. All allegations violation in stages The 2024 election is being handled, starting from from organizer Unprofessional elections, participants​ Elections that are not obedient rules , even ASN who do not neutral, when found person the alleged officer No neutral so Election Supervisory Agency NTB Province processes it in accordance rules and procedures and have also been done giving sanctions in accordance with level mistakes made​ although still there is constraint in settlement violation election.